The Association of Demographic and Risk Factors with the Degree of Photoaging Based on the Glogau Classification in Patients with Photoaging - Nayla Valinka Almira; Trisniartami Setyaningrum; Novira Widajanti (Indonesian Journal of Global Health Research, 2026)
Skin aging is influenced by intrinsic biological processes and extrinsic factors, including ultraviolet (UV) radiation, pollution, smoking, and dietary habits. In tropical countries such as Indonesia, chronic exposure to intense sunlight accelerates photoaging and increases the risk of skin damage. However, studies using standardized photoaging classifications in Indonesian populations, particularly in Surabaya, remain limited. This study aimed to analyze the association between demographic characteristics and risk factors with the degree of photoaging based on the Glogau classification among patients attending the dermatology outpatient clinic of Dr. Soetomo General Hospital, Surabaya, from January 2018 to December 2024. A retrospective descriptive-analytic study was conducted using medical records of patients diagnosed with photoaging. Total sampling was applied, and of 326 identified cases, 231 met the inclusion criteria and were included in the analysis. Data collected included age, sex, occupation, UV exposure, smoking status, coffee and alcohol consumption, clinical manifestations, Glogau classification, and treatment modalities. Data were analyzed descriptively using frequencies and percentages, while associations between demographic characteristics, risk factors, and photoaging severity were evaluated using Chi-square, Fisher’s Exact, and Linear-by-Linear Association tests with a significance level of p < 0.05. Most patients were female (97.8%), aged 20–<45 years (51.9%), and indoor workers (97.4%). Significant UV exposure was reported by 92.2% of patients, whereas smoking (5.2%) and alcohol consumption (0.4%) were uncommon. Pigmentary changes (87.0%) and wrinkles (67.5%) were the most frequent clinical features, and Glogau II was the most prevalent classification (42.9%). Age and smoking were significantly associated with increased photoaging severity, while sex, occupation, coffee intake, and alcohol consumption showed no significant associations. These findings highlight the importance of early prevention, adequate sun protection, and smoking cessation to reduce the risk of photoaging in tropical populations.